The method of multicriteria analysis for the prioritization of innovations in the construction industry - Malara, Zbigniew; Miśko, Rafał (Zielona Góra: Faculty of Economics and Management Press)
The construction industry is a vital sector that contributes to the economy`s development. On the other hand, it also contributes to the natural environment through emissions and waste. Moreover, the construction industry is under pressure to develop and adopt new technologies, tools and practices. A proper tool for selecting innovation is needed. This paper presents MCDA tool for construction companies, namely the Bellinger method. The proposed tool facilitates decision-making because it helps to choose between alternatives.
Keywords: MCDA; innovation; construction sector